If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4x + 9) + 2(3x + 8) = x + -1(9x + -5) Reorder the terms: -3(9 + 4x) + 2(3x + 8) = x + -1(9x + -5) (9 * -3 + 4x * -3) + 2(3x + 8) = x + -1(9x + -5) (-27 + -12x) + 2(3x + 8) = x + -1(9x + -5) Reorder the terms: -27 + -12x + 2(8 + 3x) = x + -1(9x + -5) -27 + -12x + (8 * 2 + 3x * 2) = x + -1(9x + -5) -27 + -12x + (16 + 6x) = x + -1(9x + -5) Reorder the terms: -27 + 16 + -12x + 6x = x + -1(9x + -5) Combine like terms: -27 + 16 = -11 -11 + -12x + 6x = x + -1(9x + -5) Combine like terms: -12x + 6x = -6x -11 + -6x = x + -1(9x + -5) Reorder the terms: -11 + -6x = x + -1(-5 + 9x) -11 + -6x = x + (-5 * -1 + 9x * -1) -11 + -6x = x + (5 + -9x) Reorder the terms: -11 + -6x = 5 + x + -9x Combine like terms: x + -9x = -8x -11 + -6x = 5 + -8x Solving -11 + -6x = 5 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -11 + -6x + 8x = 5 + -8x + 8x Combine like terms: -6x + 8x = 2x -11 + 2x = 5 + -8x + 8x Combine like terms: -8x + 8x = 0 -11 + 2x = 5 + 0 -11 + 2x = 5 Add '11' to each side of the equation. -11 + 11 + 2x = 5 + 11 Combine like terms: -11 + 11 = 0 0 + 2x = 5 + 11 2x = 5 + 11 Combine like terms: 5 + 11 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 2(1.5x-2.1)+1.7=2(2.4x-3.5) | | 2x-5x+10=-11 | | 5(5y-100)=25 | | 1x^2-12x+44=0 | | -94=2(-7r+2) | | -3(4x+9)= | | -(3b-15)=(b+5) | | 5c-15= | | 2x-(-6x)-(4-2x)=3(x+2) | | 9a+37+8=0 | | 0.5t-0.2=-2.6-0.4(2t+7) | | -5+16=m-8 | | 12=x(x)-9x+23 | | 0.14y+0.05(y+3000)=1860 | | 13+295c-20=29 | | (3x+1)=76 | | 1x^2+12x+44=0 | | 5x+5-4x=14 | | 5(1-7b)=110 | | 11+6x=3(2x+4) | | 25-2x=15+8x | | 0.5t-0.2=2.6-0.4(2t+7) | | 7=x(x)-9x+23 | | x=0.5+2.25x | | 1.3x=2x+8 | | -(4-8b)=12 | | 4x-4=3x+4 | | 3w-4w-2=12 | | 7+29a-30=-9 | | -12m=-71 | | 4x^2-82x+210=0 | | 6x-4=2x+1 |